2016
DOI: 10.1016/j.jhep.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ceramides dissociate steatosis and insulin resistance in patients with non-alcoholic fatty liver disease

Abstract: Similar increases in liver fat and NASH are associated with a metabolically harmful saturated, ceramide-enriched liver lipidome in 'Metabolic NAFLD' but not in 'PNPLA3 NAFLD'. This difference may explain why metabolic but not PNPLA3 NAFLD increases the risk of type 2 diabetes and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
358
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 378 publications
(385 citation statements)
references
References 47 publications
24
358
2
1
Order By: Relevance
“…1. Modified with permission from [7] contrast to 'obese/metabolic NAFLD', where saturated and monounsaturated triacylglycerols and NEFA predominate [47]. Insulin resistance inducing ceramides synthesised by the de novo ceramide synthetic pathway are increased in 'obese/metabolic NAFLD' but not in NAFLD associated with the I148M variant ('PNPLA3 NAFLD').…”
Section: Heterogeneity Of Nafld: Nafld But No Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…1. Modified with permission from [7] contrast to 'obese/metabolic NAFLD', where saturated and monounsaturated triacylglycerols and NEFA predominate [47]. Insulin resistance inducing ceramides synthesised by the de novo ceramide synthetic pathway are increased in 'obese/metabolic NAFLD' but not in NAFLD associated with the I148M variant ('PNPLA3 NAFLD').…”
Section: Heterogeneity Of Nafld: Nafld But No Metabolic Syndromementioning
confidence: 99%
“…Such selected patients might include those who have NAFLD but do not have dyslipidaemia or insulin resistance. Given that both the gene variants and obesity/metabolic syndrome are common, many patients of course have 'double trouble' [47].…”
Section: Heterogeneity Of Nafld: Nafld But No Metabolic Syndromementioning
confidence: 99%
“…Although IHTGs are commonly associated with IR, triglycerides (TGs) themselves are inert and do not confer IR (7). We have previously shown in humans that IR cosegregates with hepatic ceramides, independent of IHTGs and obesity (7).…”
mentioning
confidence: 99%
“…In such study, the liver lipidome was analysed from tissue obtained from liver biopsies in 125 subjects who were divided into similarly sized groups based on median HOMA-IR ('high vs. low HOMA-IR', n=62 and n=63) or PNPLA3 genotype (PNPLA3 148MM/MI, n=61 vs. PNPLA3 148II, n=64). The results of this study showed that for the 'high HOMA-IR' vs. 'low HOMA-IR' group comparison, in the more insulin resistant group (the high HOMA-IR group) the liver was markedly enriched with saturated and monounsaturated triacylglycerols and free fatty acids, dihydroceramides (markers of de novo ceramide synthesis) and ceramides [49]. Clearly, the results of this study suggest that further work is needed to better understand hepatic processing and re-modelling of liver lipids such as ceramides, and how ceramides cause hepatic insulin resistance in people with genotypes such as PNPLA3 148MM that is known to influence liver disease in NAFLD.…”
Section: Hepatic Lipid Accumulation Insulin Resistance Insulin Cleamentioning
confidence: 79%
“…Although in the past, it was thought that ceramide was simply a structural molecule, there is some evidence that increases in membrane ceramide may cause insulin resistance [48], potentially providing a mechanism to link hepatic lipid metabolism and hepatic inflammation. Recently, it has been suggested that differences in ceramide metabolism may also explain why NAFLD with insulin resistance is associated with features of the metabolic syndrome; whereas the patatin-like phospholipase domain-containing protein 3 (PNPLA3 148MM) genotype associated with NAFLD, is not associated with metabolic syndrome (and thereby with no increased risk of type 2 diabetes) [49]. In such study, the liver lipidome was analysed from tissue obtained from liver biopsies in 125 subjects who were divided into similarly sized groups based on median HOMA-IR ('high vs. low HOMA-IR', n=62 and n=63) or PNPLA3 genotype (PNPLA3 148MM/MI, n=61 vs. PNPLA3 148II, n=64).…”
Section: Hepatic Lipid Accumulation Insulin Resistance Insulin Cleamentioning
confidence: 99%